Efectos del virus bsv virus estriado del banano en la economía del productor bananero - Aguilar Nagua, Alili Alexandra (2006)
The cultivation of the banana tree represents one of the main economic items for our county, in The Gold they exist around 45 000 sowed hectares and that they have a production annual average of 1 750 boxes/hectáres/yers, cultivation that is affected by a series of plagues and illnesses that limit its production during its development. The virus BSV Grooved Virus of the Banana tree, is other causing of the loss of the production like economic of the Banana plantations, then as first it passed in the fight against this illness, you outlines the objective of:  To determine the lost one economic for effect of the virosis in the Banana plantation. To carry out this work he/she was and one scores the I number of plants "Mother given birth to with son, given birth to Mother, Mother with son, alone Mother and Son" affected by the Grooved Virus of the Banana tree), knowing the bathroom by means of the visual observation, of this infestation by means of symptoms that are characteristic of this illness. By means of the monthly ratio this value multiplied for the number of plants with virosis to obtain the real values in number of boxes lost by BSV. Reason why this same value multiplied for the cost of the box of Banana tree and we will obtain the result that it is equal to the lost one economic (cost for the lost of plants) which represents a lost one significant in the economy of the banana producer.